Violence in the workplace: a case study of construction companies in the Shah Alam area / Jashpal Kaur Bhatt - Kaur Bhatt, Jashpal (Research Management Institute (RMI), 2005)
The phenomenon of workplace violence has increasingly come under scrutiny in many developed countries. The effects of workplace violence are well documented from the perspective of the employer and employee, society in general and even on a country's economic well-being. This research project was undertaken to fill the current void in statistics from developing countries in relation to workplace violence. It consisted of a survey of construction companies in the Shah Alam area. Company and employee profiles, reported incidents of harassment, threats and assaults together with the attendant issues of employer responses and employee concerns over their safety were also considered. Lastly the scope of employment, occupational safety and health and social security laws with reference to our international commitments were also examined.